2019
DOI: 10.1088/2631-8695/ab4b00
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and optimization of AA7075 matrix surface composites using Taguchi technique via friction stir processing (FSP)

Abstract: In the present research, work is carried out for the parametric effects like tool rotation speed, tool profile and reinforcement in friction stir processing (FSP) of AA7075 on the microhardness and microstructural properties. The experiment design was carried out using Taguchi L 9 orthogonal array with three factors at three levels. Three different tool pin profiles viz. circular, triangular and square were used to experiment. The AA7075 matrix material was reinforced with SiC, RHA, and B 4 C. The tool rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…AMMC can be fabricated through various processes ranging from liquid metallurgy processing and solid metallurgy processing, some liquid metallurgy processing are compos casting, stir casting, liquid infiltration etc. [4]. Out of all liquid metallurgy processing ways out there, stir casting is one of the most flexible as it allows us react in case of change, less expensive and have the higher production rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…AMMC can be fabricated through various processes ranging from liquid metallurgy processing and solid metallurgy processing, some liquid metallurgy processing are compos casting, stir casting, liquid infiltration etc. [4]. Out of all liquid metallurgy processing ways out there, stir casting is one of the most flexible as it allows us react in case of change, less expensive and have the higher production rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…FSP is majorly used for the introduction of certain reinforcement particles in a material leading to the production of a surface composite that results in an improvement in properties of the material. According to the latest research, the process parameters contribute a lot towards microhardness of surface composites of FS processed materials, confirming that the most influential process parameters are rotational speed, reinforcement type and tool profile [35]. It was concluded that B4C should be considered as a better reinforcement material in comparison to SiC and RHA for improving the microhardness value of the composites, the value increased by 1.5 to 1.6 times from that of the workpiece material.…”
Section: Microstructural Evolutionmentioning
confidence: 88%
“…Several studies are carried out to find out the optimal process parameters for FSP/FSW using various techniques such as the Taguchi technique, response surface methodology (RSM), etc. 10,11 Mallieswaran et al 10 employed RSM for designing the number of experiments for the FSW process. It is observed that the developed regression model is capable of giving the optimal values of process parameters.…”
Section: Introductionmentioning
confidence: 99%